2022
DOI: 10.1097/md.0000000000028882
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of levetiracetam in the treatment of pediatric epilepsy

Abstract: Background: To systematically collect, critically evaluate, and synthesize current evidence with respect to the efficacy, safety, and tolerability of levetiracetam as mono-or adjunctive therapy for children and adolescents with all types of epilepsy.Methods: The presentation of methods and results in this systematic review was performed according to the evaluation guidelines for health care interventions provided in the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Protocol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…Due to its effectiveness and good tolerance, levetiracetam has recently been increasingly used as a drug of first choice–monotherapy in the treatment of epileptic seizures, especially focal and bilateral clonic-tonic seizures. Numerous studies confirmed a significant reduction of seizures in children on polytherapy due to focal, myoclonic, generalized seizures and juvenile myoclonic epilepsy ( 10 ). It has also been shown to be effective treatment for patients in status epilepticus ( 11 , 12 ).…”
Section: Discussionmentioning
confidence: 94%
“…Due to its effectiveness and good tolerance, levetiracetam has recently been increasingly used as a drug of first choice–monotherapy in the treatment of epileptic seizures, especially focal and bilateral clonic-tonic seizures. Numerous studies confirmed a significant reduction of seizures in children on polytherapy due to focal, myoclonic, generalized seizures and juvenile myoclonic epilepsy ( 10 ). It has also been shown to be effective treatment for patients in status epilepticus ( 11 , 12 ).…”
Section: Discussionmentioning
confidence: 94%
“…It has a unique site in the brain, which is the synaptic vesicle protein (SV2A), to act on achieving its antiepileptic effect. Levetiracetam regulates the function of SV2A by decreasing the vesicle release rate [ 19 ]. Intravenous levetiracetam can be given to patients who cannot tolerate oral levetiracetam, and its’ peak plasma concentration is reached in only 5-15 minutes.…”
Section: Discussionmentioning
confidence: 99%